Kualitas Fisik Cangkang Telur Ayam Arab dengan Ransum Kombinasi Azolla microphylla dan Sumber Mineral Kalsium Berbeda - Eudia Christina Wulandari; Wahyuni H I; Suthama N (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2019)
The aim of the present research was to evaluate the contribution effect of calcium derived from Azolla microphylla and different mineral sources on egg shell in Arab hen. Ninety six birds of Arab hen, age was + 16 weeks, with an average body weight of 814,73 g ± 46,86 g were used as experimental animals, and were divided randomly into a randomized block design with 6 treatments and 4 replications. Feedstuffs used for dietary treatments were rice bran, yellow corn, poultry meat meal, Azolla microphylla, CaCO3, Ca2HPO4, oyster shell, palm oil, and top mix. The rations were formulated approximately iso metabolizable energy and iso protein of 3100 kkal/kg and 17% respectively. Inclusion levels of Azolla microphylla 6% in the ration were categorized as treatments, namely, Azolla microphylla 6% without different mineral source (T1); Azolla microphylla 6% and 3% CaCO3 and 6% oyster shell (T2); Azolla microphylla 6% and 3% Ca2PO4 and 6% oyster shell (T3). Conclusion of the research is that calcium retentions are not inhibited by the Azolla microphylla, moreover it can increase calcium deposited in egg shell. Keywords: Arabian chicken, eggshell, Azolla micophylla, mineral